The complete mitochondrial genome of Ctenolepisma villosa (Insecta: Zygentoma, Lepismatidae). Issue 1 (2nd January 2019) - Chen, Bing; Dong, Fangyuan; Fang, Weixi; Xu, Jiaoyang; Gu, Yanyan; Li, Mengzhu; Sun, Entao
Abstract: In this study, the complete sequence of the mitochondrial DNA (mtDNA) of Ctenolepisma villosa was obtained using next-generation sequencing approaches and de novo assembly. The molecule was found to be 15, 488 bp in length. It is the fourth complete mt genome sequence from the Zygentoma. The mt genomes are circular and encode 37 genes and a large non-coding region. The overall structure (gene number, orientation, and order) of the mt genomes is the same as that found in three other sequenced species. All protein-coding sequences except cox1 start with the typical ATN codon. Cox1 begins with TTG, which may be a common codon in Zygentoma insects. Stem-loop structure can be observed in the largest non-coding region thought to be involved in the regulation of replication and transcription of the mitochondrial genome.